2009
DOI: 10.1016/s1734-1140(09)70100-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androsterone on convulsions in various seizure models in mice

Abstract: It is believed that a deficiency of androgens, including free testosterone, may promote the development of convulsions. The present study revealed differences in the action of androsterone (AND), a major excreted metabolite of testosterone and a neurosteroid, in three commonly used seizure models in mice. AND administered intraperitoneally exhibited dose-dependent protection against tonic-clonic convulsions caused by maximal electroshock (MES) with ED(50) (effective dose(50)) of 227 mg/kg. The compound also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Somewhat related, the influence of male sex hormones on seizures is not well understood. Studies have shown that androgens have an anticonvulsant activity, although some studies have reported conflicting results, whereby testosterone increased the frequency and severity of seizures . Independent of sex hormones, exposure to females in estrus may cause stress in male dogs, which could also explain its ability to precipitate seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat related, the influence of male sex hormones on seizures is not well understood. Studies have shown that androgens have an anticonvulsant activity, although some studies have reported conflicting results, whereby testosterone increased the frequency and severity of seizures . Independent of sex hormones, exposure to females in estrus may cause stress in male dogs, which could also explain its ability to precipitate seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosteroids rapidly alter neuronal excitability through interaction with neurotransmittergated ion channels of GABA A receptors 1,2. In addition, neurosteroids may also exert effects on gene expression via intracellular steroid hormone receptors.…”
Section: Introductionmentioning
confidence: 99%